New sales speak : - Sjodin, Terri L. (Wiley, 2006)
The author provides practical tips for achieving her recommendations and anecdotes to illustrate her points. New to this revised edition are sections about "elevator pitches" (how to close a deal if you're on an elevator with the one person "who could make your dreams a reality") and tales from Sjodin's workshops.